2009
DOI: 10.1007/s10549-009-0568-x
|View full text |Cite
|
Sign up to set email alerts
|

Numb protein expression correlates with a basal-like phenotype and cancer stem cell markers in primary breast cancer

Abstract: Decreased expression of Numb, resulting in activation of the proto

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 27 publications
4
50
0
Order By: Relevance
“…Decreased expression of Numb, resulting in activation of the proto-oncogene Notch1 and reduction of the tumor suppressor p53, has been demonstrated in breast cancers. Rennstam et al [32] demonstrated that the retained Numb expression was significantly correlated with ER and PR positivity, whereas Numb expression was reduced in the basal-like subtype, and there was an inverse correlation between the Numb expression levels and the CD44+CD24– CSC phenotype in breast tumors. The expression of Notch2 differed in subgroups of breast tumors by genotypes of the breast cancer-associated SNPrs11249433 [30], and Notch3 expression in breast cancer cells was stimulated by TGF beta 1, which is a major prometastatic product of osteoblasts, suggesting an association with bone metastasis [33].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of Numb, resulting in activation of the proto-oncogene Notch1 and reduction of the tumor suppressor p53, has been demonstrated in breast cancers. Rennstam et al [32] demonstrated that the retained Numb expression was significantly correlated with ER and PR positivity, whereas Numb expression was reduced in the basal-like subtype, and there was an inverse correlation between the Numb expression levels and the CD44+CD24– CSC phenotype in breast tumors. The expression of Notch2 differed in subgroups of breast tumors by genotypes of the breast cancer-associated SNPrs11249433 [30], and Notch3 expression in breast cancer cells was stimulated by TGF beta 1, which is a major prometastatic product of osteoblasts, suggesting an association with bone metastasis [33].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that NOS2 is a novel candidate prognostic marker for basal-like breast cancer and possibly a therapeutic target, whose activity could be selectively inhibited. Recently, increased expression of stem cell markers in basal-like tumors has been reported (40,64). Among them was CD44, which is the major receptor for hyaluronan.…”
Section: Figurementioning
confidence: 99%
“…NUMB is an important negative regulator of NOTCH signalling (Pece 2004, Stylianou 2006 and expression of NUMB is up-regulated by androgen signalling in myeloblast and muscle cells (Kovacheva et al 2010, Liu et al 2012, further highlighting integration of NOTCH and androgen pathways. Loss of NOTCH control by NUMB has been implicated in promoting a basal-like phenotype in human breast cancer (Pece 2004, Rennstam et al 2009), as has the stabilisation of p53 in response to NUMB (Colaluca et al 2008) (Fig. 5).…”
Section: Integration Of Notch and Armentioning
confidence: 99%